Factors Influencing Students Being Deceived in Pyramid Scheme in Malaysia - Mustaffa, Hawa Nur Sai’dah; Ishak, Nor Syahidah (UUM Press, 2024)
Since the middle of the 20th century, multi-level marketing (MLM) became a way of doing business. Unfortunately, not every MLM opportunity is a legitimate business opportunity. Many pyramid schemes, frauds plotted to part the unwary from their money, are disguised. The syndicate activities behind the MLM had targeted university students to make a profit through participation in their business. Therefore, this study intended to measure the factor that might affect the involvement of students being duped in pyramid schemes, including the ambitious, desire to try, surrounding society, family background, and deceived by advertising. This study examines the relationships between the ambitious with being duped in pyramid schemes. This study employed a quantitative method where a questionnaire is used as a method in the collection of the data. The hypothesized relationships are tested using survey responses from 119 university students in Malaysia. The finding of the study revealed that two determinants had a positive relationship being deceived in pyramid schemes among the students: family background and surrounding society. This study’s findings are able for universities and industries can revise their policies to discern the extent of student involvement in the pyramid scheme businesses and take the initiative to help students who fall into this scheme.